Aberrant Ki‐67 expression through 3′UTR alternative polyadenylation in breast cancers. Issue 3 (26th January 2018) - Yan, Hong; Tian, Rui; Wang, Wei; Zhang, Min; Wu, Jing; He, Jie
Abstract : Ki‐67 (MKI67) is a marker of cellular proliferation of cancer. Here, we show that Ki‐67 is post‐transcriptionally regulated through alternative polyadenylation (APA) and microRNAs in breast cancer. We show that shortening of the Ki‐67 3′UTR results in the loss of the binding sites for the suppressive miRNAs and thus renders the transcript with a shortened 3′UTR insusceptible to miRNA‐mediated suppression. This APA‐mediated shortening of the Ki‐67 3′UTR contributes to increased mRNA stability and enhanced translational efficiency. In summary, our results not only highlight the post‐transcriptional regulation of Ki‐67 involving APA and microRNAs but also suggest that Ki‐67 3′UTR disruption could serve as a molecular marker in breast cancer. Abstract : In breast cancer cells, shortening of Ki‐67 3′UTR through alternative polyadenylation (APA) results in the loss of the binding sites for suppressive miRNAs, thus rendering transcripts with shortened 3′UTR insusceptible to miRNA‐mediated suppression. This APA‐mediated shortening of the Ki‐67 3′UTR contributes to increased mRNA stability and enhanced translational efficiency.